Comparison of Code-Mixing and Code-Switching in Identity Representation on Youtube - Asni, Sukria (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2025)
This study aims to analyze the comparison between code-mixing and code-switching in two YouTube videos by the same creator when discussing national and international figures. The research uses a quantitative descriptive approach with the support of interpretative qualitative analysis within the framework of digital sociolinguistics. The data consist of utterances in the two videos, which were fully transcribed, then identified and classified based on linguistic units and their frequency of occurrence was counted. The results of the study show that the video discussing international figures exhibits the frequency of English code-mixing nearly three times higher, with 85 instances, compared to the video discussing national figures, which had 28 instances. Structurally, both videos are dominated by word-level code-mixing. These findings indicate that language choice in digital media functions as a symbolic strategy in representing both global and local identities. English functions as a symbolic capital reflecting a cosmopolitan orientation, while Indonesian represents domestic cultural solidarity. Keywords: code-switching; code-mixing; digital identity; sociolinguistics; YouTube